Health status of the aged in a selected rural and semi-urban area in the Kadugannawa MOH division - Tennakoon, H.S.B (My University, 1992)
Althourgh several of the elders were impaired in the performance of day to day activities, only a few could not attend to personal care activities. A high percentage were having poor vision and chronic diseases. Only a small percentage of them were found to be having severe degree of dementia and depression. But a significant proportion of them had the milder forms of those conditions. Their social status was very poor and a very high percentage of them had low level of contact with social activities except for the religious activities. Chronic diseases, poor mental status and lower social contacts were more marked in semi-urban areas than that of rural areas.